Touch-Interactive Flexible Sustainable Energy Harvester and Self-Powered Smart Card - Ferreira, Guilherme (2020)
G.F. and S.G. contributed equally to this work. This work was partially financed by FEDER funds through the COMPETE 2020 Programme and National Funds through FCT under the project Grant No. UID/CTM/50025/2019. NewFun (Grant ERC-StG-2014 ). DIGISMART (Grant ERC-AdG-2018).